Spatially Resolved Circumgalactic Medium around a Star-forming Galaxy Driving a Galactic Outflow at z ≈ 0.8 - Ahmed Shaban; Rongmon Bordoloi; John M. O’Meara; Keren Sharon; Nicolas Tejos; Sebastian Lopez; Cédric Ledoux; L. Felipe Barrientos; Jane R. Rigby (The Astrophysical Journal)
We report the small-scale spatial variation in cool ( T ∼ 10 ^4 K) Mg ii absorption detected in the circumgalactic medium (CGM) of a star-forming galaxy at z ≈ 0.8. The CGM of this galaxy is probed by a spatially extended bright background gravitationally lensed arc at z = 2.76. The background arc continuously samples the CGM of the foreground galaxy at a range of impact parameters between 54 and 66 kpc. The Mg ii absorption strengths vary by more than a factor of 2 within these ranges. A power-law fit to the fractional variation of absorption strengths yields a coherence length of 5.8 kpc within this range of impact parameters. This suggests a high degree of spatial coherence in the CGM of this galaxy. The host galaxy is driving a strong galactic outflow with a mean outflow velocity ≈ −179 km s ^−1 and mass outflow rate ${\dot{M}}_{out}\,\geqslant \,6{4}_{-27}^{+31}$ M _⊙ yr ^−1 traced by blueshifted Mg ii and Fe ii absorption lines. The galaxy itself has a spatially extended emission halo with a maximum spatial extent of ≈33 kpc traced by [O ii ], [O iii ], and H β emission lines. The extended emission halo shows kinematic signatures of corotating halo gas with solar metallicity. Taken together, these observations suggest evidence of a baryon cycle that is recycling the outflowing gas to form the next generation of stars.